Spin dynamics of two-dimensional systems in strong-coupling regime - Anastasiia Pervishko (2016)
A possibility to use the spin properties of the particles opens an alternative path for the creation of new devices for information storage and transfer, which in comparison to the currently existing charge-based devices have several manufacturing benefits such as a compact size of the systems and ability of easy-going state control. Additionally apart from strongly applied motives, the study of particle spin dynamics has a significant fundamental potential for the understanding of the nature of spin-induced effects. Speaking about the difficulties of spin usage, note that initial spin alignment can be lost with time under the multiple scattering events and various interactions in the absence of external influences, which regarding device manufacturing results in the information loss. For that reason, the study of the spin dynamics and the search for alternative particles, which can carry the information for relatively long time are the topics of high priority nowadays. The current thesis is devoted to the theoretical study of the spin transport effects in two-dimensional systems in strong-coupling regime. Following discussion covers several aspects of the spin dynamics and, in particular, includes: investigation of the spin and the transport properties of two-dimensional electrons dressed by laser field; investigation of polariton spin dynamics in diffusive regime; investigation of the effect of spin control in polariton systems using the effect of polariton Rabi oscillations.